2020
DOI: 10.1097/hnp.0000000000000377
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Acupressure on Symptoms Relief and Improving Sleep Quality in Pediatric Patients With Allergic Rhinitis

Abstract: Current pharmacological management of allergic rhinitis cannot completely provide relief from the symptoms and is usually accompanied by undesirable side effects. Complementary and alternative medicine approach has been evaluated and applied for allergic rhinitis frequently. We aim to investigate whether acupressure could be used as daily nursing care practice to reduce the severity of allergic rhinitis symptoms and improve sleep quality in pediatric patients with allergic rhinitis. Patients were divided into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The literature included in this study all implemented pediatric tuina on common nasal acupoints (such as Yingxiang, Bitong, Yintang, and others) to improve nasal redness, hot flashes, and local qi and blood circulation. Lei et al also confirmed that the pediatric tuina of Bitong and Yingxiang significantly improved the nasal symptoms of children with AR ( 42 ). The included literature applied distal acupoint selection to treat children with AR, particularly the special acupoints below the elbows and knees of the limbs, including the lung meridian and spleen meridian ( 29 , 30 ).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The literature included in this study all implemented pediatric tuina on common nasal acupoints (such as Yingxiang, Bitong, Yintang, and others) to improve nasal redness, hot flashes, and local qi and blood circulation. Lei et al also confirmed that the pediatric tuina of Bitong and Yingxiang significantly improved the nasal symptoms of children with AR ( 42 ). The included literature applied distal acupoint selection to treat children with AR, particularly the special acupoints below the elbows and knees of the limbs, including the lung meridian and spleen meridian ( 29 , 30 ).…”
Section: Discussionmentioning
confidence: 86%
“…Forest plot for the treatment of nasal itching symptom. Yingxiang significantly improved the nasal symptoms of children with AR (42). The included literature applied distal acupoint selection to treat children with AR, particularly the special acupoints below the elbows and knees of the limbs, including the lung meridian and spleen meridian (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…Mechanisms of acupuncture for AR have also been extensively studied. Lei RL and colleagues [ 19 ] demonstrated that acupuncture exhibits anti-inflammatory and antihistaminic effects by effects by downregulating proinflammatory cytokines and neuropeptides. A recent review [ 42 ] summarized that acupuncture modulates anti-inflammatory actions in AR through various pathways, including upregulating Th1 cytokines, downregulating Th2 and proinflammatory cytokines, and affecting proinflammatory neuropeptides and neurotrophies.…”
Section: Discussionmentioning
confidence: 99%
“…It is a well-established complementary and alternative therapy with a long history of use in use in treating various diseases in China. As a subtype and noninvasive alternative to acupuncture, which has been demonstrated to be effective and safe for PAR [ 8 ], acupressure is easy to administer and has been widely used for clinical treatment in mainland China, Taiwan, Hong Kong, South Korea, Germany, and Australia [ 15 19 ]. Two meta-analyses [ 16 , 17 ] have indicated that acupressure for AR is both safe and effective.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation